UPAYA PENGAWAS DALAM PEMBINAAN PROFESIONAL GURU IPS PADA MADRASAH IBTIDAIYAH NEGERI KOTA BANJARMASIN - Noor Hidayati (Universitas Lambung Mangkurat, 2018)
AbstractTeacher as the spearhead and one of the components that play a role in determining the quality of education, must always improve his knowledge and skills through the help of orther professionals, namely supervisors. The purpose of this study is to determine the efforts of supervisors in development of social studies teacher is profesionalism in MIN Banjarmasin and the factors that influence it. This research uses qualitative descriptive method. Data are obtained through interview, observation, and documentation. The results of this study indicate that (1) Supervisors efforts in fostering social studies teacher profesionalsm in MIN Banjarmasin based on programs that were prepared with other supervisors. Coaching efforts are still focused on class visits, interviews and meetings by using a collaborative approach. (2) These influencing factors are that supervisors rarely get training in supervision, that teacher is still reluctant to solve the problem and does not want to be supervised in class, the lack of teacher responsibility even though he has passed the teacher certification and lack technical skills and limited means.Keywords: Suopervisor, Coaching, Profesionalism, Social studies teacherAbstrakGuru sebagai ujung tombak dan satu komponen yang berperan dalam menentukan kualitas pendidikan, harus selalu meningkatkan pengetahuan dan keterampilannya melalui bantuan orang lain yang profesional, yakni Pengawas. Tujuan penelitian ini untuk mengetahui upaya-upaya yang dilakukan pengawas dalam pembinaan profesional guru IPS pada MIN kota Banjarmasin serta faktor-faktor yang mempengaruhinya. Penelitian ini menggunakan metode deskriptif kualitatif. Data diperoleh melalui wawancara, observasi, dan dokumentasi. Hasil penelitian ini menunjukakan bahwa (1) upaya pengawas dalam membina profesional guru IPS pada MIN Kota Banjarmasin didasarkan pada program yang disusun bersama pengawas lainnya. Upaya pembinaan masih terfokus kepada kunjungan kelas, wawancara dan rapat dengan menggunakan pendekatan kolaboratif. (2) Faktor-faktor yang mempengaruhinya, yaitu pengawas jarang mendapatkan diklat dan pelatihan tentang kepengawasan, guru masih kurang mau menyelesaikan masalahnya dan tidak mau disupervisi kelas, rendahnya tanggung jawab meskipun lulus sertifikasi guru, serta kurang penguasaan skill teknologi dan sarana terbatas.Kata Kunci: Pengawas, Pembinaan, Profesional, Guru IPS